2015
DOI: 10.7589/2014-05-119
|View full text |Cite
|
Sign up to set email alerts
|

SEROLOGIC, TRACE ELEMENT, AND FECAL PARASITE SURVEY OF FREE-RANGING, FEMALE MULE DEER (ODOCOILEUS HEMIONUS) IN EASTERN WASHINGTON, USA

Abstract: Blood and fecal samples collected from 97 free-ranging mule deer (Odocoileus hemionus), from four distinct herds during the spring of 2000 or 2001 in eastern Washington, US, were tested for exposure to selected pathogens, concentrations of trace elements, and presence of parasites in feces. Antibodies were detected to the following: Leptospira interrogans serovar Bratislava (4%), Leptospira interrogans serovar Canicola (1%), Leptospira interrogans serovar Grippotyphosa (13%), Bovine viral diarrhea virus 1 (57%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 36 publications
0
15
0
1
Order By: Relevance
“…Myers et al (2015) sampled mule deer ( O . hemionus ) sera in Washington for BVDV antibody and found similar seroprevalence in 2000 (53%) and 2001 (59%), suggesting little variability with year [ 40 ]. White-tailed deer may be exposed only sporadically to BVDV depending upon site and/or year and we may not have sampled during a year with obvious exposure.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Myers et al (2015) sampled mule deer ( O . hemionus ) sera in Washington for BVDV antibody and found similar seroprevalence in 2000 (53%) and 2001 (59%), suggesting little variability with year [ 40 ]. White-tailed deer may be exposed only sporadically to BVDV depending upon site and/or year and we may not have sampled during a year with obvious exposure.…”
Section: Discussionmentioning
confidence: 99%
“…In 2011, prevalence was 36%, but dropped to 2% and 7% in 2012 and 2013, respectively, so the interaction between year and site was significant, indicating that seroprevalence varies independently on each site on a yearly basis. Myers et al (2015) also found a difference in seroprevalence for PI3 with study site in the same year for mule deer [ 40 ]. Since both deer and cattle have been shown to transmit PI3 [ 20 ], perhaps deer and/or cattle are maintaining PI3 in the populations separately between the two study sites.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations